PENERAPAN METODE LATIHAN UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR - Andik Sulistio (DIADIK, 2024)
The objectives of this study are: (1) to describe the application of the application of the training method in order to increase students' readiness for PJOK subjects at SD Negeri 02 Air Rami. (2) describe the application of training methods in improving student achievement in PJOK subjects at SD Negeri 02 Air Rami. (3) To describe the effectiveness of the application of the training method in improving student achievement in the subjects of PJOK SDN 02 Air Rami, Mukomuko Regency. Academic Year 2022/2023. Data collection techniques used in the study were observation sheets and student test methods. Analysis of the data used values ​​are 1) Analysis of Student Attention, (2) Analysis of Pre-test and Post-test, (3) Analysis of the t test of Student Achievement. The conclusions of this research are; (1) The application of the training method can increase students' attention to the PJOK subject at the 02 Air Rami State Elementary School. (2) With the implementation of the student learning achievement training method, there is an increase in PJOK subjects at the Air Rami 02 State Elementary School. (3) With the implementation of the training method in learning on PJOK subjects, it is very effective in increasing students' attention and learning achievement at Air Rami 02 State Elementary School